Information needs of cancer patients and survivors regarding diet, exercise and weight management: a qualitative study. (3rd December 2013) - James‐Martin, G.; Koczwara, B.; Smith, E.L.; Miller, M.D.
<x xml:space="preserve">Abstract</x> While advanced cancer is often associated with weight loss, curative cancer treatment is often associated with weight gain. Weight gain during treatment may be associated with greater risk of cancer recurrence and development of lifestyle diseases. Currently, limited resources are available to cancer patients focussed on weight control. This study assessed the information needs of patients undergoing curative chemotherapy regarding diet, exercise and weight management for the purpose of developing weight management resources. Focus groups were held with oncology practitioners, patients and survivors to determine current information provision and needs. Focus groups highlighted a perception that information provision regarding diet, exercise and weight management is insufficient and no routine assessment of weight occurs during chemotherapy. Barriers to information provision described included lack of resources and time, and practitioners' uncertainty regarding appropriate messages to provide. Patients wanted more information regarding diet, exercise and weight during treatment time. The findings of this study suggest an increase in provision of diet, exercise and weight management information is needed. This information should be evidence‐based and delivered at an appropriate time by the preferred health care professional. It would also be beneficial to implement protocols regarding assessment of weight during treatment.